The influence of hospital practices and family support on breastfeeding duration, adverse events, and postnatal depression among first-time mothers - Dib, Sarah; Fewtrell, Mary; Wells, Jonathan C. K.; Mohd Shukri, Nurul Husna (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Baby-friendly hospital practices and family support are recognised to improve the chances of successful breastfeeding. The associations between support and maternal psychological state and breastfeeding problems are less explored. This study aimed to assess the influence of professional and family support on breastfeeding adverse events and postpartum depression at 2 weeks and exclusive breastfeeding (EBF) status at 12 weeks postpartum, and to identify predictors of positive outcomes. Methods: 64 primiparous Malaysian mothers were interviewed face-to-face, at 2, 6 and 12 weeks post-delivery, to collect data regarding family support, hospital and infant feeding practices, breastfeeding problems and pain, maternal perceptions and depression. Logistic regression and correlation were used to ascertain associations between support and EBF, adverse events and postpartum depression. Results: Neither professional nor family support predicted EBF at 12 weeks. Eighty-five percent of the mothers received high family support, which was associated with lower depression scores (r=-0.36, p=0.005); higher depression scores were associated with more breastfeeding problems. EBF discontinuation before 12 weeks was predicted by maternal perception of insufficient milk supply (OR=8.96, CI=1.78, 45.18). Earlier breastfeeding initiation (r=0.26, p=0.04) and skin-to-skin contact (r=0.25, p=0.048) were associated with lower breastfeeding pain. EBF in hospital was correlated with fewer breastfeeding problems (r=0.31, p=0.01). Conclusion: Mothers with greater family support suffered from less depressive symptoms, which could lower the incidence of breastfeeding problems and prolong EBF duration. Skin-to-skin contact, early breastfeeding initiation and EBF in hospital were associated with less adverse events, thus better compliance with these Baby-Friendly practices is recommended.